Turmeric/ Oregano extracts as wound healing agents in a diabetic animal model - Sami, Diana Guirguis (AUC Knowledge Fountain, 2019)
Diabetic wound infections and pressure ulcers pose a significant challenge to healthcare providers worldwide. With an increased incidence of chronic skin ulcers and a significant financial impact on healthcare systems, reaching $25 billion annually, new methods to treat chronic and diabetic ulcers are in great need. The current study provides new and innovative wound care products that reduce inflammation, clear infection and improve healing time in an animal model of pressure and diabetic ulcers. Animal model with excisional wound & pressure ulcer was done on the dorsal side of the rats in diabetic and non-diabetic groups. Our results showed that pressure ulcer had significantly different pathological features compared to excisional wounds. Diabetes caused skin changes that negatively affects the healing process. Different turmeric extracts, oregano essential oil and chitosan nanoparticles were tested for their antibacterial & antioxidant activity. Results showed that turmeric ethanolic extract 5%, oregano essential oil 1% & chitosan nanoparticles 1% had the most antibacterial & antioxidant effects. Ointments were synthesized of each herb individually. An in vivo pilot study was conducted on diabetic and non-diabetic rats with pressure ulcer. Results showed that turmeric 5% ointment successfully healed the ulcer in both diabetic and non-diabetic rats by day 15. The oregano 1% ointment achieved complete healing by day 15 in the non-diabetic group while in the diabetic group was achieved by day 21. The above concentrations were incorporated in different forms (ointment, amorphous hydrogel & nanofibers). Those forms were tested for their antibacterial, cytotoxic effect & in vivo using Tegadermïƒ¢ (commercial wound dressing) as positive control. Our results showed that the designed formulas had significant antibacterial effect as Tegadermïƒ¢. On testing the formulations on mouse fibroblast cell line (L929), ointment & hydrogel were non-cytotoxic while nanofibers showed relative cytotoxicity if compared to Tegadermïƒ¢ that was highly toxic. By testing the formulations in vivo, our results showed that by day 15 ointment and nanofibers achieved complete wound closure while hydrogel and Tegadermïƒ¢ did not.